Model of Trust Monitoring and Updating Based on Dynamic Weighted Allocation - Hu, Bin; Wu, Yuemin; Sun, Min; Bang Liu, Zheng; Zhang, Lin; Yan, Jia-Xing; Huang, Shan; Zhu, Shu-Xin (Recent Advances in Electrical & Electronic Engineering, 2019)
Backgrounds: In order to guarantee safe and efficient operation interaction in open network environment, a new dynamic trust monitoring and updating model based on behavior context is proposed in this paper. Methods: Setting four behavior attributes such as security, availability, reliability and performance. Then utilizing the fuzzy clustering and information entropy mathematical methods to carry out the effective synthesis on such attributes. Conclusion: The effectiveness and efficiency of the schema are verified by simulation.
Keywords: information entropy